The Role of Topology in Solving Differential Equations and its applications - Ms. Rinku (Innovative Research Thoughts, 2022)
The role of topology in solving differential equations refers to the use of topological concepts and methods to study the behavior of solutions to differential equations. A differential equation is an equation that relates a function and its derivatives to some independent variables. The solutions to a differential equation are functions that satisfy the equation and describe some physical or mathematical phenomena.